Field assessment of C‐POD performance in detecting echolocation click trains of bottlenose dolphins (Tursiops truncatus). Issue 1 (27th June 2014) - Roberts, Bethany L.; Read, Andrew J.
Abstract We evaluated the performance of dolphin echolocation detectors (C‐PODs) in the New River, North Carolina, by ground‐truthing echolocation detections with digital acoustic recordings. We deployed C‐PODs at three sites for a total of 204 monitoring hours. We also performed detection range trials at two sites where water depths ranged from 1.0 to 4.5 m. We used Detection Positive Minutes (DPMs), minutes of C‐POD recordings that contained at least one echolocation click train, to indicate the presence of at least one dolphin. The C‐PODs performed well in detecting dolphin click trains, although all units performed conservatively by failing to detect some echolocation events and therefore underestimated the true occurrence of dolphins. C‐PODs reported only a small number of false detections, as indicated by low false positive rates ranging between 1% and 4% for individual units. Overall, C‐PODs performed with a high accuracy (72%–91%) and detected echolocation at a distance of at least 933 m. We conclude that C‐PODs hold considerable promise in future monitoring studies of this species, but recommend a careful study design especially in complex, coastal environments.